The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/dmso.s303151
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 Regulates High Glucose-Induced Viability, Oxidative Stress, Fibrosis, and Inflammation in Diabetic Nephropathy via miR-325-3p/Snail1 Axis

Abstract: Background: Diabetic nephropathy (DN), as a complication of diabetes, is a leading cause of mortality in diabetic patients. It has been reported that lncRNA PVT1 (PVT1) could accelerate the progression of DN by promoting ECM accumulation and increasing the expression of fibronectin 1 (FN1). However, the underlying mechanism of PVT1 on DN remains unknown. Methods: To study the effect of PVT1 on DN, mice were injected 50 mg/kg STZ to build the DN models. Mesangial cells (MCs) were induced by high glucose as in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Recently, more and more studies have shown that long noncoding RNA (lncRNA) is involved in the pathogenesis of human diseases including DN. Qin et al reported that lncRNA PVT1 regulated HG-induced viability, oxidative stress, fibrosis, and inflammation in DN through the miR-325-3p/Snail1 axis [ 5 ]. It has been found that knockdown of lncRNA NORAD inhibits the proliferation, inflammation, and fibrosis of human mesangial cells under HG conditions by regulating the miR-485/NRF1 axis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more and more studies have shown that long noncoding RNA (lncRNA) is involved in the pathogenesis of human diseases including DN. Qin et al reported that lncRNA PVT1 regulated HG-induced viability, oxidative stress, fibrosis, and inflammation in DN through the miR-325-3p/Snail1 axis [ 5 ]. It has been found that knockdown of lncRNA NORAD inhibits the proliferation, inflammation, and fibrosis of human mesangial cells under HG conditions by regulating the miR-485/NRF1 axis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, miR-325 is predicted to be the downstream target of lncRNA MSC-AS1. MiR-325 has been found to regulate HG-induced viability, oxidative stress, fibrosis, and inflammation in DN through the mediation of lncRNA PVT1 [ 5 ]. In addition, lncRNA MSC-AS1 promoted the progression of colorectal cancer by regulating the miR-325/TRIM14 axis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The histological collagen deposition should be evaluated in addition to mesangial and glomerular areas [ 43 ]. Lastly, PVT1 may exert its effects on DN progression through other mechanisms besides ECM accumulation, such as podocyte apoptosis [ 16 ], inflammation and oxidative stress [ 44 ], and haemodynamic factors [ 45 ]. Further investigations are needed to delineate the complex network of PVT1 and its interactions with other biological molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Snail1 silence has also been revealed to decrease the polarization of M1 macrophages and alleviate the levels of in ammatory cytokines in the study on renal brosis [23]. Within diabetic conditions snail1 expression seems to be particularly upregulated and promotes oxidative stress and in ammation [24]. And snail1 silencing could effectively prevented diabetes-related complications progression [25].…”
Section: Introductionmentioning
confidence: 99%
“…Snail1, the core transcription factor acting as epithelial to mesenchymal transition (EMT) inducer, has been increasingly considered as a major regulator of macrophage activation. The action of Snail1 has been involved in multiple cellular progresses including tumor invasion and migration, brosis and in ammation [19][20][21]. Whether snail1 in uence the in ammation microenvironment and macrophage polarization has been addressed in those related studies.…”
Section: Introductionmentioning
confidence: 99%